The specifics of chamber measurements of greenhouse gas emissions in coastal and marine ecosystems - Nesterova, Olga; Bovsun, Mariia; Yatsuk, Andrey; Kravchenko, Dmitry (Edelweiss Applied Science and Technology, 2024)
The article presents the results of measuring CO2 fluxes on the beach in areas with and without marine macrophytes and at the water-atmosphere boundary in Kievka Bay. Such studies were conducted for Kievka Bay for the first time. A chamber dynamic method and a laser gas analyzer were used to measure CO2 fluxes at all plots. Higher values of CO2 fluxes were noted on the beach in areas with dry beach macrophytes compared to wet beach macrophytes. Areas with macrophytes had 23 times higher values of CO2 fluxes compared to areas without beach macrophytes. To identify patterns and intensity of CO2 gas exchange between the sea and the atmosphere, long-term monitoring measurements are necessary, since there are many variable factors. When measuring gas exchange between the sea and the atmosphere, sharp short-term increases or decreases in CO2 concentration were noted on the graphs of concentration versus measurement time. This was not associated with technical failures of the gas analyzer or features of the floating chamber. This introduces difficulties in interpreting the data, since the linearity of the graph is lost and the error in the flow value increases.